Power efficiency at distributed computing utilizing mobile devices - Mamchych, O. O.; Volk, M. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The goal of this work is to build a principal model of power consumption measurement of distributed computing in the cloud of mobile devices. The goal is to make a scheduling algorithm based on a map-reduce approach - a heuristic runtime scheduling algorithm that takes into account not only power consumption of computing devices, but also network transmission power consumption and expenses on additional security overhead. The algorithm is supposed to be an extension of existing heuristic algorithm, but in addition to computing time estimation it will also estimate power consumption.
Keywords: information technology; data processing; mobile devices; data centers